PENGARUH PEMBIAYAAN JUAL BELI DAN PEMBIAYAAN BAGI HASIL TERHADAP PROFITABILITAS BANK UMUM SYARIAH - Mohammad Rif'an Saiq, - (2018)
Penelitianinibertujuanuntukmemverifikasipengaruhpembiayaanjualbelidanpembiayaanbagihasilterhadapprofitabilitaspada bank umumsyariah di Indonesia. ProfitabilitasdiukurdenganmenggunakanReturn On Assets (ROA), pembiayanjualbelidanpembiayaanbagihasildiukurdari total perolehanmarjindarisetiappembiayaan. Metodepenelitian yang digunakanadalahmetodedeskriptifdanverifikatif. Sampelpadapenelitianiniberjumlah 63 data observasidari 9 Bank UmumSyariah di Indonesia selamaperiode 2011-2017.Metodepengumpulan data dalampenelitianinidilakukandenganteknikdokumentasi. Teknikpengolahan data dilakukandengananalisisregresi linier bergandadenganbantuanEviews 9. Hasilpenelitianmenunjukkanbahwapembiayaanjualbeliberpengaruhsignifikanpositifterhadapprofitabilitasdanpembiayaanbagihasiltidakberpengaruhterhadapprofitabilitas;---This research aimed to verification the effect of sale and purchase financing and profit sharing financing toward profitability of Islamic Commercial Bank in Indonesia. Profitability was measured by Return On Assets (ROA), sale and purchase financing and profit sharing financing were measured by margin gain from each financing. The method of this research is used descriptive and verificative. The sample of this research is 63 observation data from 9 islamic banks in Indonesia during the period of 2011-2017. Method of data collecting in this research done by documentation technique. Data processing technique is done by multiple linier regression analysis with Eviews 9. The results of this research show that sale and purchase financing have positif significant effect to profitability and profit sharing financing have no effect to profitability.